Evaluating the Special Needs of The Military for Radiation Biodosimetry for Tactical Warfare Against Deployed Troops: Comparing Military to Civilian Needs for Biodosimetry Methods. Issue 2 (August 2016) - Flood, Ann Barry; Ali, Arif N.; Boyle, Holly K.; Du, Gaixin; Satinsky, Victoria A.; Swarts, Steven G.; Williams, Benjamin B.; Demidenko, Eugene; Schreiber, Wilson; Swartz, Harold M.
Abstract : Abstract: The aim of this paper is to delineate characteristics of biodosimetry most suitable for assessing individuals who have potentially been exposed to significant radiation from a nuclear device explosion when the primary population targeted by the explosion and needing rapid assessment for triage is civilians vs. deployed military personnel. The authors first carry out a systematic analysis of the requirements for biodosimetry to meet the military's needs to assess deployed troops in a warfare situation, which include accomplishing the military mission. Then the military's special capabilities to respond and carry out biodosimetry for deployed troops in warfare are compared and contrasted systematically, in contrast to those available to respond and conduct biodosimetry for civilians who have been targeted by terrorists, for example. Then the effectiveness of different biodosimetry methods to address military vs. civilian needs and capabilities in these scenarios was compared and, using five representative types of biodosimetry with sufficient published data to be useful for the simulations, the number of individuals are estimated who could be assessed by military vs. civilian responders within the timeframe needed for triage decisions. Analyses based on these scenarios indicate that, in comparison to responses for a civilian population, a wartime military response for deployed troops has both more complex requirements for and greater capabilities to use different types of biodosimetry to evaluate radiation exposure in a very short timeframe after the exposure occurs. Greater complexity for the deployed military is based on factors such as a greater likelihood of partial or whole body exposure, conditions that include exposure to neutrons, and a greater likelihood of combined injury. These simulations showed, for both the military and civilian response, that a very fast rate of initiating the processing (24, 000 d −1 ) is needed to have at least some methods capable of completing the assessment of 50, 000 people within a 2‐ or 6‐d timeframe following exposure. This in turn suggests a very high capacity (i.e., laboratories, devices, supplies and expertise) would be necessary to achieve these rates. These simulations also demonstrated the practical importance of the military's superior capacity to minimize time to transport samples to offsite facilities and use the results to carry out triage quickly. Assuming sufficient resources and the fastest daily rate to initiate processing victims, the military scenario revealed that two biodosimetry methods could achieve the necessary throughput to triage 50, 000 victims in 2 d (i.e., the timeframe needed for injured victims), and all five achieved the targeted throughput within 6 d. In contrast, simulations based on the civilian scenario revealed that no method could process 50, 000 people in 2 d and only two could succeed within 6 d.